Estruturação administrativa da contratação de conciliadores e mediadores judiciais - Moreira, Aline Simonelli (2019)
The abovementioned decision on conciliation and judicial mediation relations, in order to obtain the necessary legal and judicial restrictions on the provision of legal services. Specifically, the aim is to discuss how to hire, who to hire as remuneration and how to fund, developing a suitable model for the hiring of professionals. Thus, the Brazilian courts, as well as the entire public administration, face financial problems and limits of personnel expenses, the regulations of Law 101/2000, which should prevent public utilities from being used to compose the conciliators and mediators (CPC/15), is it possible to identify a national substitute and a possibility of hiring conciliators and mediators from a positive legal framework.